Effects of Periodontal Disease Knowledge and Awareness of Scaling on Scaling Fear in Adults - Seul-gi Kim; Soon-Ryun Lim (치위생과학회지)
Background: Gingivitis and periodontal disease are common conditions requiring early management. Regular scaling prevents periodontal disease but is often avoided due to pain and discomfort, leading to worsened conditions. Dental fear, particularly related to scaling, is a significant barrier; however, few studies have explored it. This study aimed to identify the factors that influence scaling fear in adults. Understanding these factors will enable dental professionals to mitigate these fears and promote regular scaling. Methods: An online survey was conducted, targeting adults aged 19 years and older with prior scaling experience. Using convenience sampling, 270 responses were analyzed. The survey included 30 items measuring general characteristics, periodontal disease knowledge, scaling awareness, and scaling fear. Data were analyzed using IBM SPSS version 23.0 (IBM Corp., Armonk, NY, USA) with multiple regression to identify factors affecting scaling fear. Results: The mean scores were 4.76±1.35 for periodontal disease knowledge, 3.82±0.55 for scaling awareness, and 2.87±0.63 for scaling fear. Scaling awareness (β=–0.236, p＜0.001), periodontal disease knowledge (β=–0.157, p=0.01), and the number of scaling sessions in the past two years (β=–0.147, p＜0.05) significantly influenced scaling fear. Conclusion: Scaling awareness and periodontal disease knowledge are key to reducing fear of scaling. Dental professionals should educate patients and provide clear explanations to build trust and create positive experiences. Oral health education programs should be expanded to improve awareness, reduce fear, and foster regular scaling attendance.